Prevalence of post-endodontic flare-ups and host-related factors - Siraj DAA Khan; Mohammed Saeed Alabbas; Hassan Salem Alyami; Khalid Dhafer Al-Yami; Hadi Hamad Al-Alyami; Fahad Yahya Alswaidan; Ahmad Mohammed Almakrami; Yassin Mana M Algfenh (Amaltea Medical Publishing House, 2023)
Background. Root canals feature a high incidence of post-treatment flare-ups, characterized by pain, swelling, or discomfort following endodontic procedures, which remain a concern in dental practice. This study aims to evaluate the host-related factors behind the prevalence of post-endodontic flare-ups. Methodology. A retrospective study was conducted on the records of 93 patients who were treated endodontically between January 2017 and December 2021. Data extracted from records included age, medical conditions, diagnosis, and tooth type. SPSS 27.0 was used to analyze the data. Multivariate logistic regression analysis was employed to identify significant predictors while controlling for potential confounding factors. Results. The flare-up rate among patients who had received endodontic treatment was 31.2% in the study population. Multivariate logistic regression analysis demonstrated that age and the presence of a vital pulp were significant predictors of flare-ups. Older patients exhibited an increased likelihood of experiencing flare-ups (p 0.05). Conclusion. The study provided insights into the frequency of post-endodontic flare-ups and the impact of host-related factors on their occurrence. Age and vital pulp were found to be important predictors, highlighting the significance of individualized treatment planning. These results highlight the possibility of improved patient outcomes through a thorough understanding of post-endodontic problems and contribute to evidence-based endodontic practice.